1 Zn-doped ZIF-67 as catalyst for the CO2 fixation into cyclic carbonates. (July 2017) - Zanon, Adriano; Chaemchuen, Somboon; Mousavi, Bibimaryam; Verpoort, Francis
Graphical abstract: Highlights: Zn doped ZIF-67 was successfully synthesized at room temperature. High conversion and selectivity were achieved for CO2 conversion into cyclic carbonates. No solvent or co-catalyst are required for the cyclic carbonate formation. Complete conversion was achieved within 2 hours Abstract: A newly Zn-doped ZIF-67 has been synthesized in water at room temperature for the first time without the aid of any organic solvent. The textural and physical properties of the material were analyzed by X-ray diffraction (XRD), thermogravimetric analysis (TGA), N2 adsorption-desorption, scanning electron microscopy (SEM) and ICP-AES. The catalyst showed quantitative conversions and selectivity for the synthesis of cyclic carbonates starting from epoxides and carbon dioxide. Compared with different reported MOFs as heterogeneous catalysts used for the cycloaddition of carbon dioxide to epoxides, this catalyst outperforms all the reported ones till now. The coupling reaction was studied at different pressures and temperatures applying different epoxide substrates. Additionally, no co-catalyst and solvent were required to obtain excellent conversions. The heterogeneous nature of the catalyst was maintained at least up to four catalytic cycles with a slight loss of activity.